Determinants of variations in sleep patterns across Brazil: Exploring geographic influences - Giovana Longo-Silva; Renan Serenini; Roberto Antunes; Márcia Lima; Anny Pedrosa; Risia Menezes (Sleep Medicine: X)
Objective: To examine the influence of latitude, longitude, sunrise, and daylight, in conjunction with individual and behavioral factors, on sleep duration, wake time, and bedtime in a country with the world's broadest latitude range, yet characterized by homogeneity in language, cultural traits, and consistent time zones. Methods: Participants (n = 1440; 18-65y) were part of a virtual population-based survey (2021–22). Sleep patterns were spatially represented through maps using Multilevel B-spline Interpolation. Relationships between and within biological/personal/socio-economic, behavioral and environment characteristics, and sleep outcomes were examined by Lasso regression. Restricted cubic splines were employed to examine the shape of the association of latitude and sunrise with sleep variables and of screen time before bed with bedtime. Results: Latitude emerged as the primary geographic factor influencing variations in sleep duration and wake time, shortening and advancing, respectively, as latitude increased (towards equatorial line). Younger individuals, those living without partners, with depression, engaging in more frequent evening alcohol consumption, and with poorer diet quality, tended to wake up later. All the variables influenced bedtime, with daylight emerging as the environmental factor exerting the strongest association. While the variability in bedtime showed a non-linear association with latitude and sunrise, it displayed a dose-response relationship with screen time before bed. Conclusions: Given that adults living in the same country, potentially with a similar timetable, could be having shorter sleep durations according to their latitude position, further studies are required to contemplate advocating for policies that implement schedules based on the sun position rather than the national time zone.